A context-based approach to community interpreting. Perceptions and expectations about professional practice in the Spanish context. - Ciordia, Leticia Santamaría (International Journal of Language, Translation and Intercultural Communication, 2016)
The paper provides an overview of the evolution of the community interpreter’s profile in the direction of a more inclusive, participatory role were the effectiveness of the message and success of the communication rely on the basis of cooperation, empathy and mediation skills. On the basis of an empirical study carried out in medical and legal settings, this paper reflects on the perceptions and expectations among both service providers and interpreting practitioners about the interpreter’s role, and the competences and the degree of involvement that should be expected as a result. The findings suggest that a gap seems to exist between real-life practices and standards of behaviour on paper, which are so limiting that they oblige the interpreter to ‘step out’ of the normative role. A correlation also seems to exist between the interpreter’s attitudes and the level of professionalization of community interpreting; in this sense, attention will be payed to the impact that current lack of regularisation in countries such Spain has on the interpreter’s performance. Finally, the author singles out clients´ expectations and the nature of the interpreted encounter as key paradigms in determining the interpreter’s involvement, and concludes that it is not an entirely free choice on the part of the interpreter, but also and significantly a reaction to the expectations of the clients about which role is considered appropriate in a given setting.